2023
DOI: 10.1021/acs.jafc.2c08275
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Improves Bone Microenvironment-Related Hematopoiesis and Immunity in T-2 Toxin-Exposed Mice

Abstract: The T-2 toxin is one of the most frequent contaminants in the environment and agricultural production globally. It exerts a wide range of toxic effects. Selenium (Se), as an antioxidant, has the potential to be widely used to antagonize mycotoxin toxicity. To investigate the protective effects of Se on bone microenvironment (BM)-related hematopoiesis and immunity after T-2 toxin exposure, 36 male mice were treated with the T-2 toxin (1 mg/kg) and/or Se (0.2 mg/kg) by intragastric administration for 28 days. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…40 Moreover, T-2 toxin is stable in nature and difficult to completely remove from food and feed, which poses a serious threat to human and animal health. 41 Also, T-2 toxin can cause liver DNA breakage, 42 induce liver oxidative stress and apoptosis, 9,12,43 and induce the expression of liver inflammatory factors, leading to liver injury, 32 which seriously endangers the health of animals and humans. However, there is no effective antagonist to alleviate liver injury caused by T-2 toxin due to the lack of key targets and corresponding drugs for the liver injury.…”
Section: ■ Discussionmentioning
confidence: 99%
“…40 Moreover, T-2 toxin is stable in nature and difficult to completely remove from food and feed, which poses a serious threat to human and animal health. 41 Also, T-2 toxin can cause liver DNA breakage, 42 induce liver oxidative stress and apoptosis, 9,12,43 and induce the expression of liver inflammatory factors, leading to liver injury, 32 which seriously endangers the health of animals and humans. However, there is no effective antagonist to alleviate liver injury caused by T-2 toxin due to the lack of key targets and corresponding drugs for the liver injury.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Combined with the KEGG enrichment analysis results of the T-2 group vs. the control group, it was shown that the T-2 toxin could induce apoptosis, whereas SeMet indirectly antagonized apoptosis. Oxidative stress and apoptosis have been shown to occur in mice exposed to the T-2 toxin, and apoptosis was alleviated after treatment with Se [ 46 ]. Moreover, the apoptosis pathway was significantly enriched in the T-2 + SeMet group vs. the T-2 group, and the autophagy pathway appeared simultaneously.…”
Section: Discussionmentioning
confidence: 99%